Note of Excavations at 'Grimes Graves,' Norfolk (Proceedings of the Society of Antiquaries of Scotland, 1871)
Lord Rosehill gives a report on Rev Canon Greenwell’s excavation of “Grimes’ Gaves” in Norfolk. He describes the site, the process of excavation and what was found as it progressed. Some of the artefacts found at the site are described by the author. Lord Rosehill agrees with Rev Greenwell’s assessment that this site is a neolithic flint mine.